PMMA nanocomposites with graphene oxide hybrid nanofillers - J. Sanes; G. Ojados; R. Pamies; M. D. Bermudez (eXPRESS Polymer Letters)
Polymethylmethacrylate (PMMA) and nanocomposites containing 0.5 wt.% graphene oxide (GO), graphene oxide-multiwalled carbon nanotubes (NT) or graphene oxide-ionic liquid 1-octyl-3-methylimidazolium tetrafluoroborate (IL) (PMMA+GO; PMMA+GO-NT; PMMA+GO-IL) were processed by a single step twin-screw micro-extrusion. The effect of two extrusion temperature profiles and two specific mechanical energy (SME) values has been studied. Results of Raman spectroscopy, scanning electron microscopy (SEM) and transmission electron microscopy (TEM), energy dispersive X-ray analysis (EDX), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS) analysis show changes in GO composition and morphology, and better dispersion due to interaction with IL. Dynamic mechanical analysis shows that extrusion conditions affect storage modulus of hybrid nanocomposites. Rheological measurements show that the complex viscosity of the nanocomposites is higher than that of PMMA at low shear rates for materials processed under the lower value of SME. A maximum viscosity increase of 62.6% is found for PMMA+GO-NT. The lowest increase found for PMMA+GOIL, is attributed to the better dispersion of the hybrid GO-IL nanofiller.